The structuring of the "United States of Europe": Myth or Reality? (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
The present paper studies the problems and debates about the constitutional nature of the Treaty establishing a European Constitution. The principal argument is the defenceof a United States of Europe from the point of view federal. For that is analysed the different federal elements founded in the constitutional text.
Keywords: European Constitution; European integration; supranacionalism and intergubernamentalism